SYNTHESIS DAN CHARACTERIZATION OF C-4-HYDROXY-3-ETHOXYPHENYL CALIX[4]RESORCINARENE SULFONATE - Handayani, Desi Suci; Sholikh, Riska Azizawati; Kusumaningsih, Triana (Alchemy Jurnal Penelitian Kimia, 2013)
The synthesis of C-4-hydroxy-3-methoxyphenyl calix[4]resorcinarene sulfonate using vanillin as a starting material has been done. The synthesis was carried out in two steps i.e. (1) acid-catalyzed cyclization resorcinol with vanillin and (2) sulfonation C-4-hydroxy-3-methoxyphenyl calix[4]resorcinarene. Product were analyzed their structure with FTIR and1H NMR also characterized their melting point and solubility. The results showed that product have melting point more than 300 oC and more soluble in aquadest than organic solvents.